The relative frequency of Rossby wave train triggering mechanisms associated with downstream development over europe - Thornton, Colin L. (Monterey, California. Naval Postgraduate School, 2014)
Rossby wave trains (RWTs) are coherent envelopes of baroclinic waves that propagate on the midlatitude waveguide and are capable of producing downstream development. The waveguide is a region of heightened potential vorticity gradient along steeply sloping isentropic surfaces defining the mid-latitude jet stream. The goal of this research is to examine a climatology of objectively identified RWTs that result in downstream development over Europe, and to develop a methodology to subjectively determine the atmospheric phenomena responsible for triggering each. The purpose is to provide insight into the relative frequency of occurrence of RWTs triggered by each of four atmospheric disturbances over the North Atlantic to support future research into improving the predictability of waveguide perturbations and subsequent downstream development. A subset of RWTs is analyzed using dynamic tropopause, upper-level divergent outflow, sea level pressure, and Hovmöller plots. The RWT triggering mechanisms are identified and, when applicable, compared to known occurrences in climatology. Twenty-seven are (71%) are triggered by warm conveyor belts associated with extratropical cyclones, three (8%) by tropopause polar vortices, two (5%) by the extratropical transition of tropical cyclones, and six (16%) by diabatic Rossby vortices. Approved for public release; distribution is unlimited. Lieutenant, United States Navy http://archive.org/details/therelativefrequ1094542739